Diseño e implementación de una fábrica de columnas de hierro electrosoldado destinadas a la construcción civil. - Morales Bres, Inti Rafael (2010)
The region of Loja and all Ecuador are now growing in the field of low houses construction, and the process used to make iron columns for these buildings is not always adequate. The main of the project we present here is to improve the fabrication of iron columns with Engineering helps and industrial production lines processes that allows to get a high quality in the products, with uniform measures and strong behave with the concrete. Thus we want to set up a columns making plant, with structural and electrical calculations, and experimental work in order to observe the present methods of fabrication and be able to compare it with our project. Additionally we are going to draft a security handbook for the staff who will work in the factory.